Rekrutmen Partai Golkar Pada Pemilu Legislatif 2019 - Achmad Cumaedy; Riska Sarofah (Jurnal Pemerintahan dan Politik Lokal, 2019)
This study describes the Golkar Party recruitment process in the 2019 Legislative Election with a case study of the allocation of seats in the Tangerang Districts A and B districts. The problem of recruitment has an impact on the distribution of legislative candidates in allocating DPRD seats, in PKPU RI Number 16 Year 2017 Concerning the Arrangement of Electoral Districts and Chair Allocation Members of the Regency/City Regional People's Representative Council in the General Election, that the seat allocation is a determination of the number of seats in an electoral district. This study used qualitative methods by conducting in-depth interviews and literature studies through sources relevant to this research. The results of the study show that the Golkar Party recruitment pattern is still using the old pattern, namely by using the recruitment system during the new order and trying to retain traditional (old) voters. In the upcoming recruitment, Golkar must involve various elements in the community and the beginning of the recruitment must start from the "grassroots" which can gradually occupy the party management positions. Keywords: Recruitment, Golkar Party, Seat Allocation, and Electoral District.